DIRECTIONS FOR INCREASING LABOR PRODUCTIVITY IN AGRICULTURE - Ubraimov Shuhratjon Rakhimberdievich; Sidikov Dilmurod Hasanboy oglu; Rashidov Rahmatullo Alojonovich (Galaxy International Interdisciplinary Research Journal, 2022)
For the development of any society, it is required to increase labor productivity in enterprises and organizations in all sectors and branches of the economy of this society. In order to increase labor productivity, it is necessary to effectively use all types of economic resources in the production process. It is very important to choose the way to use these economic resources, to achieve an increase or decrease in the volume of products produced without increasing their consumption. It is necessary to study the experiences of managers in economically developed countries on increasing labor productivity. They operate under the motto "install a faster working machine, lighten the work, increase the level of specialization of work, then the productivity will increase".